Analysis of Sedimentation as Implications of Beach Accretion using Spatial Analysis in the Coastal Area of Banyuasin South Sumatra, Indonesia - Yulifa Handayani; Robiyanto H Soesanto; Fauziyah Fauziyah; Eddy Ibrahim; Muhammad Hendri; Ngudiantoro Ngudiantoro (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
This study was conducted in the coastal area of ​​Banyuasin (CAB) which was considered to have a variety of sedimentation classes originating from fluvial and marine processes. The study aimed to observe/determine changes in the morphology of coastal areas related to sedimentation in the CAB and to make maps related to oceanographic parameters, changes in the land cover and identification of the distribution of sedimentation occurring in the CAB, and the dominant factors influencing the change. This study used imagery interpretation method and the sediment data collection used sediment traps to determine the occurrence of accretion and abrasion. The results of the study showed that there was a change in the environment based on the analysis of Landsat imagery, that have undergone changes are Ekor Tikus island (PET), Tg Api-api (TAA), and the Bungin River (SB), which are affected by the land conversion, sedimentation, and tidal currents. There has been an environmental change in the CAB, especially at the Banyuasin estuary (PET) with a high sedimentation rate. The changes also occurred in TAA and SB, with the dominant factor being the decline in mangrove forests. As a result, it is necessary to conduct a more detailed study and time series related to mangroves.